Prevalence and Associated Factors of Dizziness Among a National Community-Dwelling Sample of Older Adults in India in 2017–2018 - Pengpid, Supa; Peltzer, Karl (Makara Journal of Health Research, 2021)
Background: This study aimed to determine the prevalence and associated factors of dizziness in older community-dwelling adults in India. Methods: The cross-sectional sample was composed of 21,343 individuals (≥65 years) from the Longitudinal Aging Study in India (LASI) Wave 1 in 2017–2018. Dizziness was assessed by determining if the individuals suffered from “persistent or troublesome dizziness or light headedness” in the past 2 years. Results: Women and men had the overall prevalence of 14.6%/17.2% and 11.6% in past 2-year dizziness, respectively. Adjusted logistic regression analysis revealed that sociodemographic factors (female sex), physical chronic conditions (angina), geriatric conditions (incontinence and impaired vision), stress and mental health (poor or fail self-rated health, perceived discrimination, neurological or psychiatric problems, insomnia symptoms, persistent headaches, and severe fatigue or exhaustion) and health risk behavior (tobacco use) were positively associated with dizziness. Conclusions: One in seven older adults in India had past 2-year dizziness. The factors associated with dizziness included female sex, angina, incontinence, impaired vision, poor or fair self-rated health, perceived discrimination, neurological or psychiatric problems, insomnia symptoms, persistent headaches, severe fatigue or exhaustion, and tobacco use.